2024
DOI: 10.1161/cir.0000000000001163
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Management of Patients After Cardiac Arrest: A Scientific Statement From the American Heart Association and Neurocritical Care Society

Karen G. Hirsch,
Benjamin S. Abella,
Edilberto Amorim
et al.

Abstract: The critical care management of patients after cardiac arrest is burdened by a lack of high-quality clinical studies and the resultant lack of high-certainty evidence. This results in limited practice guideline recommendations, which may lead to uncertainty and variability in management. Critical care management is crucial in patients after cardiac arrest and affects outcome. Although guidelines address some relevant topics (including temperature control and neurological prognostication of comatose survivors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 281 publications
(432 reference statements)
1
8
0
Order By: Relevance
“…2 Manifestations of PCAMD include hypotension and ventricular systolic/diastolic dysfunction, resulting in reduced cardiac output, arrhythmias, and pulmonary edema. 3,31 In this study, abnormal but inconsistent electrocardiogram manifestations, as well as histological injury with myocytolysis and myocardial fibrosis, could be found at 24 hours after ROSC. These findings indicated the presence of acute myocardial dysfunction, which reduced the cardiac output and consequent decreased systemic perfusion.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…2 Manifestations of PCAMD include hypotension and ventricular systolic/diastolic dysfunction, resulting in reduced cardiac output, arrhythmias, and pulmonary edema. 3,31 In this study, abnormal but inconsistent electrocardiogram manifestations, as well as histological injury with myocytolysis and myocardial fibrosis, could be found at 24 hours after ROSC. These findings indicated the presence of acute myocardial dysfunction, which reduced the cardiac output and consequent decreased systemic perfusion.…”
Section: Discussionsupporting
confidence: 51%
“…8 Optimize vital organ perfusion, reduce the risk of EMOD, and support organ function are fundamental and effective managements to increase the likelihood of intact neurological survival after resuscitation. 3,9 To date, no therapeutic-related factors, including targeted temperature management, have shown a clear association with positive outcome after ROSC. 2,3,10 Additionally, no pharmaceutical interventions have been proved to be effective for improving neurological outcome after CA, 7 and the molecular mechanisms underlying the pathogenesis of PCABI are still poorly understood, which reminds us further investigating mechanisms of PCABI/PCAS to search new drug targets, as well as identifying novel biomarkers that can monitor the development and predict the outcome of PCABI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These insights provide a nuanced understanding of the complex interplay between CPR, particularly chest compression, and lung health. These findings underscore the need for careful consideration of CPR techniques and the potential need for tailored ventilation strategies in the immediate post-resuscitation period to mitigate the risk of CRALE and subsequent ALI and to improve patient outcomes [14,17,18,49,50]. The definitions and characteristics of CRALE are detailed in Figure 2.…”
Section: Cardiopulmonary Resuscitation-associated Lung Edema (Crale)mentioning
confidence: 98%
“…Guidelines on post-resuscitation care suggest adopting a protective ventilation strategy to prevent VILI and aiming for a tidal volume of 4-8 mL/kg/ideal body weight to avoid overdistention; a PEEP level guided by the monitoring of airway pressures as a surrogate of compliance so that excessive pressure is avoided (i.e., keeping plateau pressure < 30 cmH2O and driving pressure < 15 cmH2O); and a respiratory rate kept in a range between 8 and 16 breaths/min. In the comatose patient, the post-resuscitation goal remains, however, avoiding both hyperoxia and hypoxia and maintaining both normoxia, i.e., PaO2 10-13 kPa, and normocapnia, i.e., PaCO 2 4.5-6 pKa [14,17,18,49,50,64]. Nevertheless, in these patients, maintaining normocapnia with protective ventilation can be challenging due to the risk of using high PEEP together with increased dead space ventilation; often, hypercapnic acidosis occurs and can be particularly detrimental in the instance of cerebral injury, although the recent TAME trial has shown that targeting mild hypercapnia after cardiac arrest does not account for adverse neurological outcomes [65,66].…”
Section: Ventilation Strategies and Alimentioning
confidence: 99%